Prolonging IOP-lowering effect of glaucoma surgery - I.B. Alekseev; A.I. Samoylenko; А.К. Aylarova (РМЖ "Клиническая офтальмология")
Currently, glaucoma surgery is considered as primary but not reserve treatment option. The paper reviews historical aspects of glaucoma surgery, important milestones of technique development, and domestic and foreign published data on major surgical procedures for glaucoma, complications of glaucoma filtering surgery, and methods to prevent postoperative scarring. Special attention is paid to glaucoma surgical procedures. It was demonstrated that sinus trabeculectomy is more effective than non-penetrating procedures after 6 and 12 months. Complications of sinus trabeculectomy, risk factors for filtering bleb scarring, and diagnosis of novel pathway obliteration (which reduces the efficacy of glaucoma filtering surgery) are discussed. Recent approaches to prevent filtering bleb scarring using implants, drainage devices, and cytostatic agents are addressed. In Russia, antimetabolite administration is limited since these drugs are not approved for subconjunctival injections. Bleb needling revision is the most promising, simple, and minimally invasive technique to prevent scarring after fistulizing procedures.  Keywords: glaucoma, glaucoma surgery, sinus trabeculectomy, filtering bleb, needling revision, complications, optical coherence tomography.  For citation: Alekseev I.B., Samoylenko A.I., Aylarova А.К. Prolonging IOP-lowering effect of glaucoma surgery. Russian Journal of Clinical Ophthalmology. 2019;19(2):93–98. About the authors: 1Igor B. Alekseev — MD, PhD, Professor of the Department of Ophthalmology, ORCID iD 0000-0002-3906-0479; 2Alexander I. Samoylenko — MD, PhD, Head of Vitreoretinal Department, ORCID iD 0000-0002-5796-6012; 1Agunda K. Aylarova — postgraduate student of the Department of Ophthalmology, ORCID iD 0000-0002-9709-4693. 1Russian Medical Academy of Continuous Professional Edu- cation. 2/1, Barrikadnaya str., Moscow, 125993, Russian Federation. 2S.P. Botkin City Clinical Hospital, Branch No. 1, Ophthalmological Clinical Hospital. 7, Mamonoskiy Lane, Moscow, 123001, Russian Federation Contact information: Agunda K. Aylarova, e-mail: agundaailarova@mail.ru. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 02.03.2019.